Pengaruh ROE, ROA, Dan Price Book To Value Terhadap Harga Saham Perusahaan Manufatur Di BEI - Miranti Rumaisa; I Made Murjana; Baiq Desthania Prathama (Kredibel: Jurnal Ilmiah Manajemen, 2023)
This study aims to analyze the effect of Return On Equity (ROE), Return On Assets (ROA), and Price Book To Value (PBV) partially and simultaneously on stock prices and the most dominant influence is Return On Equity (ROE), Return On Assets (ROA), and Price Book To Value (PBV) for stock prices in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for 2018-2021. The population in this study amounted to 26 companies with a sampling technique using purposive sampling so that the number of samples was 15 companies. The analytical method used is multiple linear regression analysis. The results of the multiple linear regression analysis are Y = 7,771 + 3,697 X1 - 11,841 X2 + 0,120 X3. The results showed that partially the ROE variable had a non-significant positive effect on stock prices, ROA had a significant negative effect on stock prices, and PBV had a significant positive effect on stock prices. Simultaneously the variables ROE, ROA, and PBV also affect stock prices. The most dominant variable is indicated by the PBV variable.